Axial and Lateral Crushing of Elliptical Composite Tubes - Alkoles, Omar M. Saleh (2003)
Reduce structural weight, design flexibility, and improved structure safety, are the features offered by composite materials. Composite materials provide higher or equivalent crash resistance as compared with their metallic counterparts and therefore find use in applications involving crash. The design of various transport vehicles like automobiles and aircraft for crashworthiness, required collapse behaviour of structural component and energy absorption characteristics An experimental and computational study of woven roving composite circular and elliptical cross section Subjected to quasi-static axial and lateral-loading conditions was carried out in this project. Composite tubes with different ellipticity ratio alb from 1 .00 to 2.00 were investigated under three different loading conditions. The effect of geometry and loading condition on the load carrying capacity, energy effect of geometry and loading condition on the load carrying capacity, energy absorption capability and their failure mechanism histories are presented and discussed. Finite element models were developed to predict the load carrying capacity, failure mechanism, deformed shapes and stress contours of composite elliptical tubes under different loading conditions. From the Experimental result, the ellipticity ratio significantly affects the load carrying capacity and t he energy absorption capability 0 f t he tubes on both three loading conditions. The tubes subjected to axial loading condition showed a stable load deformation curve, higher initial failure load and higher energy absorption capability, compared to the tubes subjected to lateral loading conditions. Experimental result for tubes under axial load show that the tube with ellipticity ratio of a/b=LOO has the highest initial crush failure load of 42.45 leN, tubes with ellipticity ratio a/b= 1.25, 1.50, 1.75, and 2.00 have the initial failure load of 40.65 kN, 40.45 kN, 36.65 kN, and 36.46 kN respectively. Under lateral loading condition (L W) the tube with ellipticity ratio a/b=2.00 has the highest initial crush failure load of 1768 N, and has the highest specific energy absorption of 0.70 kj/kg, the initial crush failure load for the tubes with ellipticity ratio a/b=1.75, 1.50, 1.25, and a/b=1.00 are 1545 N, 1060N, 922 N, and 873 N respectively. For specimens loaded on lateral side (LN) show that the tube with ellipticity ratio aJb=2.00 has the highest initial crush failure load of 1480 N, and has the highest specific energy absorption of 0.69 kj/kg, the initial crush failure load for the tubes with ellipticity ratio a/b=1.75, 1.50, 1.25, and a/b=1.00 are 1561 N, 1074 N, 912N, and 873 N respectively. Finite element simulation predicts the initial failure load and the deformed shapes. The result for tubes under axial load show that tube with ellipticity ratio of a/b= 1.00 has the highest initial crush failure load of 49.50 kN, tubes with ellipticity ratio a/b= 1.25, 1.50, 1.75, and 2.00 have the initial failure load of 45.40 kN, 41.30 kN, 36.40 kN, and 32.70 kN respectively. For lateral loading (LW) the tube with ellipticity ratio a/b=2.00 has the highest initial crush failure load of 2915 N, the initial crush failure load for the tubes with ellipticity ratio aib=1.75, 1.50, 1.25, and a/b=1.00 are 2657 N, 2232 N, 1805 N, and 1377N respectively. For Lateral loaded on narrow side (LN) the tube with ellipticity ratio aib=2.00 bas the highest initial crush failure load of 2150 N, the tubes with ellipticity ratio a/b=1.75, 1.50, 1.25, and a/b=1.00 have initial crush failure load of 1821 N, 1604 N, 1617 N, and 1377 N respectively. Finite element model predictions are correlated with the experimental results. Because of the imperfection in the real tubes is not considering in the finite element model, there is different in loads value between experiment and simulation. In general predictions are quite good.